Let $(S_t)$ be a geometric Brownian Motion, i.e. $S_t = S_0 e^{\left(\mu-\frac{\sigma^2}{2}\right)t+ \sigma W_t }$. Let $\alpha>0$ and $\tau = \inf\{t>0 | S_t \geq \alpha\}$. Compute $P(\tau \leq t)$.

What I have done:

I know that for $X_t = W_t - \beta t$, $X_t^* = sup_{0\leq s \leq t} X_s$ and $\alpha \geq 0$

$$P(X_t^* \geq \alpha ) = 1- \Phi\left( \frac{\alpha + \beta t}{\sqrt{t}} \right) + e^{-2 \alpha \beta} \Phi\left( \frac{\beta t - \alpha}{\sqrt{t}} \right) $$ Furthermore, I know that $P(\tau \leq t) = P(S_t^* \geq \alpha ) $. Hence I would have started with $$ \log(S_t)= \log(S_0) + \left(\mu - \frac{\sigma^2}{ 2 }\right)t + \sigma W_t \geq \alpha $$ $$ W_t \geq \frac{ \log\left(\frac{\alpha}{S_0}\right) - \left(\mu - \frac{\sigma^2}{ 2 }\right)t}{\sigma} $$ Now I would set $$\alpha^{'} = \frac{\log\left(\frac{\alpha}{S_0}\right)}{\sigma}$$ and $$\beta = -\frac{\left(\mu - \frac{\sigma^2}{ 2 }\right)}{\sigma}$$ and would use the formula for $P(X_t^* \geq \alpha^{'} )$ as stated above. Is this correct? I am not sure and I feel like I have done something wrong. Any hints or comment welcome -thanks!

  • $\begingroup$ For deterministic $\theta_t$, $\mathbb{P}(W_t \geq \theta_t ) = 1 - \Phi(\theta_t) $. As you have already calculated, here $$\theta_t = \frac{1}{\alpha}\left(- \left(\mu - \frac{\sigma^2}{2}\right)t+\log \frac{\alpha}{S_0}\right).$$ $\endgroup$ – ChargeShivers May 6 '17 at 14:34
  • $\begingroup$ @ChrisVarghese you mean $\frac{1}{\sigma}$ don't you? But I can/should use the formula given by $P(X_t^{*} \geq \alpha)$ with my values for the cosntant $\alpha$ and the drift $\beta$ since I can rewrite my $W_t$ as $X_t = W_t + \frac{\mu - \frac{\sigma^2}{2}}{\sigma}$ define $X_t^{*} = \sup_{0\leq s \leq t} W_s$ and then plug in? $\endgroup$ – Methamortix May 6 '17 at 14:58

$$ P(\tau \leq t ) = P(S_s \geq \alpha, s \in [0,t]) = P(\log(S_0) + \left(\mu - \frac{\sigma^2}{ 2 }\right)s + \sigma W_s \geq \alpha, s \in [0,t])$$ $$=P\left( W_s \geq \frac{ \log\left(\frac{\alpha}{S_0}\right) - \left(\mu - \frac{\sigma^2}{ 2 }\right)s}{\sigma}, s \in [0,t] \right) $$

Now set $$\alpha^{'} = \frac{\log\left(\frac{\alpha}{S_0}\right)}{\sigma}$$ and $$\beta = -\frac{\left(\mu - \frac{\sigma^2}{ 2 }\right)}{\sigma}$$ Then you have $$P\left( W_s \geq \alpha^{'} + \beta s, s \in [0,t] \right) $$ Define $X_t = W_t - \beta t$ and $X_t^* = \sup_{0\leq s \leq t} X_s$ and use the formula $$P(X_t^* \geq \alpha^{'} ) = 1- \Phi\left( \frac{\alpha^{'} + \beta t}{\sqrt{t}} \right) + e^{-2 \alpha^{'} \beta} \Phi\left( \frac{\beta t - \alpha^{'} }{\sqrt{t}} \right) $$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.